Analysis of Students' Physics Literacy Skills in Solving HOTS Problems and Self-Regulated Learning - Rezeki, Nani Sri; Purba, Andre Agachi; Simangunsong, Ika Trisni (Kasuari: Physics Education Journal (KPEJ), 2024)
The purpose of this research is to examine the physics literacy skills of students solving HOTS questions and self-regulated learning (SRL) on measurement material at private high schools in Maju Village, through descriptive research using a qualitative approach. The instruments used include questionnaires, and HOTS test questions on Measurement material. The results showed that the low SRL category (score 98) was unable to reach the questions at C4. The medium group (score 120), could not fulfill all level 4 indicators. In high SRL, students are able to fulfill the indicators, by solving the problem completely, using the right information, applying numeracy skills, and being able to provide conclusions and their reasons, but cannot fulfill the indicators at level 5 and 6. The learning independence factor plays a significant role in determining the level of HOTS student.